2017
DOI: 10.1186/s13013-017-0116-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sarcopenia and degenerative lumbar scoliosis in older women

Abstract: BackgroundAge-related sarcopenia can cause various forms of physical disabilities. We investigated how sarcopenia affects degenerative lumbar scoliosis (DLS) and lumbar spinal canal stenosis (LSCS).MethodsSubjects comprised 40 elderly women (mean age 74 years) with spinal disease whose chief complaints were low back pain and lower limb pain. They included 15 cases of DLS (mean 74.8 years) and 25 cases of LSCS (mean age 72.9 years).We performed whole-body dual-energy X-ray absorptiometry (DXA) to analyze body c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 19 publications
3
56
0
Order By: Relevance
“…Sarcopenia, which is a reduction in skeletal mass, is commonly seen in patients with DLS. Eguchi et al [26], using DEXA scans to assess the appendicular and trunk skeletal muscle mass, showed that sarcopenia was present in 46.6% of the DLS patients [26]. Sarcopenia is defined as the appendicular skeletal mass index of less than 5.46 kg/m 2 [27].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…Sarcopenia, which is a reduction in skeletal mass, is commonly seen in patients with DLS. Eguchi et al [26], using DEXA scans to assess the appendicular and trunk skeletal muscle mass, showed that sarcopenia was present in 46.6% of the DLS patients [26]. Sarcopenia is defined as the appendicular skeletal mass index of less than 5.46 kg/m 2 [27].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…The appendicular skeletal mass index (ASMI) is the sum of the arm and leg lean mass (kg) divided by square of the height (m 2 ) [27]. Studies have also shown that ASMI negatively correlated with pelvic tilt [26], whereas trunk skeletal mass index (Trunk SMI) which is defined as trunk lean mass Spinal Deformities in Adolescents, Adults and Older Adults DOI: http://dx.doi.org /10.5772/intechopen.90052 divided by height 2 (m 2 ) significantly correlated with the sagittal vertical axis, pelvic tilt (PT), and lumbar scoliosis [26]. Moreover, trunk SMI correlated positively with bone mineral density (BMD), suggesting that reduction in trunk muscle mass was associated with osteoporosis and sagittal imbalance [26], which is prevalent in patients with DLS.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 3 more Smart Citations